Highly excited B, B s and B c meson spectroscopy from lattice QCD - Luke Gayer; Sinéad M. Ryan; David J. Wilson; for the Hadron Spectrum collaboration (Journal of High Energy Physics)
Abstract Excited state spectra of B, B s and B c mesons are computed using lattice QCD. Working with a large basis of carefully constructed, approximately-local q q ¯ $$ q\overline{q} $$ -like operators we determine a rich spectrum of states up to J = 4 in B, B s and B c , that can be grouped into patterns matching those of the quark model. In addition, hybrid-like states are identified at approximately 1500 MeV above the ground states in each of B, B s and B c , in a multiplet pattern already found in similar computations at a range of quark masses spanning light to bottom. This study is performed using an anisotropic, relativistic Wilson-clover action at a single spatial lattice spacing of a s ≈ 0.12 fm and with a light-quark mass corresponding to m π ≈ 391 MeV. We find good agreement with experimental results where known and discuss prospects for further work in interesting J P quantum numbers.